(3YLGFH GdMH hGdMjGI YfO GdMjhGfs - (3eMehO, eUWais 1921 - 2009 ((3GdLjRI, eUQs (3OGQ GdQGjI ddfTQ hGdJhRjYs, 2016)
(3CYLH CfhGY GdZRd(B-(3CReI GdEScGf aj YGde GdMjhGf(B-(3YGde GddUhU aj GdfHGJ hGdMjhGfs
1 2 4 5 7 11 13 14 18 20 21 22
Keywords: (3GdebGdGJ GdYQHjIs -- (3eUQs